Strengthening the Role of the Corruption Eradication Commission in Preventing Corruption through the Illicit Enrichment Approach in LHKPN Reporting: Penguatan Peran KPK dalam Pencegahan Tindak Pidana Korupsi melalui Pendekatan Illicit Enrichment pada Pelaporan LHKPN - Winharli, Khurulaini Syahwa (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Corruption remains a persistent systemic problem in Indonesia, prompting preventive strategies centered on transparency and accountability of public officials. Specific Background: The Corruption Eradication Commission (KPK) administers the State Officials’ Wealth Report (LHKPN) as a preventive instrument; however, its implementation is weakened by low compliance, data inaccuracy, and the absence of stringent sanctions. Knowledge Gap: Although Indonesia has ratified the United Nations Convention against Corruption (UNCAC), the Illicit Enrichment mechanism mandated therein has not been substantively integrated into the national legal framework to reinforce LHKPN. Aims: This study examines the prospects of incorporating the Illicit Enrichment concept into Indonesian regulations to strengthen LHKPN as an effective tool for corruption prevention. Results: The findings indicate that adopting Illicit Enrichment could enhance substantive verification of LHKPN, ensure accountability of asset disclosures, and provide a legal basis for follow-up actions against unexplained wealth. Novelty: This study offers a focused legal analysis linking Illicit Enrichment directly to the strengthening of LHKPN as a preventive mechanism rather than solely as a punitive tool. Implications: Regulating Illicit Enrichment in Indonesia would bolster the preventive mandate of the KPK, improve asset transparency, and contribute to more effective corruption deterrence through enhanced legal certainty and enforcement. Highlights: Administrative-only LHKPN sanctions weaken deterrence and reduce asset declaration accountability. Illicit enrichment criminalization enables substantive verification of abnormal wealth growth in LHKPN. Strengthened enforcement supports investigation escalation and asset recovery for unexplained wealth. Keywords: Corruption Prevention, Illicit Enrichment, LHKPN, Asset Transparency, KPK